PENGARUH PENGALAMAN KERJA DAN STRES KERJA TERHADAP BURNOUT KARYAWAN PEKERJA HARIAN LEPAS (PHL) DI RUMAH SAKIT BHAYANGKARA MAKASSAR TAHUN 2023 - Suprijadin Suprijadin; Ricky Perdana Poetra; Mohammad Ardani Samad; Fauziah Botutihe (Institut Kesehatan Pelamonia, 2026)
A successful hospital needs employees who will do more than usual, those who will provide performance that exceeds expectations. In today's dynamic world of work, where hospitals need employees who will show good citizenship behavior, such as helping other individuals in the team, volunteering to do extra tasks, avoiding unnecessary conflicts, respecting each other, enthusiasm and complying with the contents of the rules , and generously tolerating occasional work-related losses and disruptions, Burnout takes a toll on itself and the world around it. The bad impact of burnout experienced is that it disrupts interpersonal relationships, interpersonal disorders make life at work worse, it can be seen that this bad condition involves physical conditions that decrease fatigue at work, while high levels of burnout can create disturbances between individuals and work. This study aims to analyze the effect of work experience and work stress on burnout of casual daily worker employees at Bhayangkara Hospital Makassar. The type of research used in this research is quantitative research using a Cross Sectional Study design, the sampling technique used is purposive random sampling with a sample of 175 respondents, data analysis techniques using univariate and bivariate analysis. The results of the study can be concluded that there is an effect of work experience on burnout of Freelance Daily Workers (PHL) employees at Bhayangkara Hospital Makassar, a p value of 0.000, there is an effect of work stress on burnout of Freelance Daily Workers (PHL) employees at Bhayangkara Hospital Makassar, a p value of 0.000. It is suggested to the hospital to provide training and education to employees who have less work experience at Bhayangkara Makassar Hospital, and are expected to pay attention to positions according to the employee's ability to deal with the emergence of stress on workers in the hospital.